Surgical Treatment and Management of the Hernia Umbilical Riview and Update - Iqbal Wahyu Santosa; Ismi Azizah (Journal La Medihealtico, 2025)
Adult umbilical hernia repair has also undergone considerable sophistication over the last few years, shifting towards less traditional repair using the suture as the main repair material, in favor of mesh-based methods, which are more conducive to long-term biomechanical needs of the abdominal wall. This evidence-based review literature synthesises up-to-date evidence based on randomised controlled trials, systematic reviews, and recent clinical guidelines in order to compare surgical outcomes obtained using an open, minimally invasive, and robotic-assisted surgical technique. The results indicate that the mesh repair is always associated with the least recurrence rates in comparison to the suture-only closure, especially in cases when the mesh is placed in retromuscular, preperitoneal, or extraperitoneal positions; in these places, the tension-sharing support increases the durability and reduces the risk of seroma formation and adhesion. Less invasive extraperitoneal methods such as eTEP offer desirable rates of postoperative comfort and quicker recovery as compared to those offered by ENDOR with some extra advantages to hernias that come with diastasis recti by allowing the rebuilding of functional midline. Robotic repair enhances accuracy in performing more challenging dissections but depends on resource availability; the results of its repetition are similar to results with laparoscopy. The data shows that no one technique is always best, and effective repair is based on the ability to match the surgical strategy with the extent of defects, physiology, and capacity of the institution